Slope stability analysis along the proposed Kathmandu-Hetauda Road with tunnel sections - Humagain, I. R.; Schetelig, K.; Sharma, M. P.; Upreti, B. N.; Langer, M. (Journal of Nepal Geological Society, 2000)
The proposed Kathmandu-Hetauda Road alignment passes through Thankot, Chitlang, Kulekhani, Bhimphedi, and Bhaisedobhan. It is the shortest as well as least hazardous route very suitable for a standard highway. It has the following three tunnel sections: the Thankot Tunnel (3.2 km long), the Kulekhani Tunnel (500 m long), and the Chisapani Tunnel (3.8 km long). The alignment passes through the Kathmandu Nappe, Upper Nawakot Group of the Lesser Himalaya, and the Siwaliks. It also crosses the Main Boundary Thrust and the Mahabharat Thrust, four major faults/shear zones, and a major fold axis. The areas of plane sliding, wedge sliding, and toppling are delimited on the basis of the study of discontinuities along the proposed alignment. The stability analysis show s that 60-75% of the total road length is stable, 20-30% is fair, 5- 15% is weak, and 2-5% is critical.